Circular beam‐reconfigurable antenna base on graphene‐metal hybrid. Issue 7 (1st April 2016) - Cheng, Xiaohe; Yao, Yuan; Qu, Shi‐Wei; Wu, Yongle; Yu, Junsheng; Chen, Xiaodong
Abstract : The concept and analysis of a graphene‐metal beam‐reconfigurable terahertz (THz) loop antenna are presented. The hybrid graphene‐metal implementation is proposed to combine (i) dynamic surface conductivity tunability using different DC bias voltages and (ii) high radiation efficiency enabled by metal. The loop antenna which employs an artificial mu‐negative transmission line provides the horizontally polarised omnidirectional radiation. The graphene‐metal loop around the centre ring acts as a reflector. Changing the DC bias of different position of graphene to control the position of resonance can effectively adjust the beam direction. The proposed concept and achieved performance, computed using realistic material parameters, are extremely promising for beam scanning at THz frequencies.